Numerical simulation of turbulence model based on building energy enthalpy. Issue 23 (29th November 2019) - Shi, Xin; Lu, Weiding; Zhao, Ying; Fu, Jialei
Abstract : Temperature and humidity play an extremely important role in indoor thermal comfort and industrial production. To achieve precise control of temperature and humidity in the building space environment and reduce energy consumption, it is necessary to analyse turbulence from the perspective of energy. On the basis of the basic principle of building energy enthalpy, under the premise of reasonable assumptions of various boundary conditions, four turbulence models were established for simulation. The basic characteristics, overall distribution and local characteristics of the interior energy enthalpy were compared and analysed. The theory of building energy enthalpy not only can effectively solve the influence of latent heat on the building environment, but also can provide guidance on the selection strategy of turbulence models. The proposed theory can improve the accuracy and credibility of the simulation data of building space.